Stereotip dan komunikasi interpersonal antara etnis aceh dan etnis tionghoa - Nurrahmi, Febri; Putra, Ferry Gelluny (Jurnal Studi Komunikasi, 2019)
Chinese is an ethnic minority in Aceh province implementing Sharia law. This minority group gets a lot of negative stereotypes. This study looks at the reciprocal relationship between stereotypes and interpersonal communication between Acehnese and Chinese. Using Social Learning Theory, this study seeks to describe how a person's learning process through face-to-face interpersonal communication can confirm, change, and even eliminate negative stereotypes that have been previously known. This study employed an explanatory qualitative method. The data were obtained through in-depth interviews with five key informants who were Acehnese and have lived in Gampong Laksana for more than 10 years. The results of this study illustrate that, even though the informants learned many negative stereotypes of Chinese, the majority of informants were not affected by these negative stereotypes. The informants chose to trust personal experience and establish effective communication with Chinese, which eventually eliminated negative stereotypes towards the Chinese group.